2006
DOI: 10.1097/01.aog.0000202398.27428.e2
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Activity and Function in Middle-Aged and Older Women

Abstract: II-3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
181
10
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 282 publications
(219 citation statements)
references
References 28 publications
21
181
10
7
Order By: Relevance
“…These results are consistent with those reported by Broumandfar et al and Addis et al (29,30). Overall, previous research has highlighted the role of economic status in sexual dysfunction, indicating that people with low income are more likely to have sexual dysfunction (16,31).…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with those reported by Broumandfar et al and Addis et al (29,30). Overall, previous research has highlighted the role of economic status in sexual dysfunction, indicating that people with low income are more likely to have sexual dysfunction (16,31).…”
Section: Discussionsupporting
confidence: 92%
“…Obesity can be a primary cause of FSD; however it is also associated with metabolic syndrome, diabetes, and cardiovascular disorders; factors that lead to impaired sexual functioning. [12][13][14] In consistence with our findings, previous studies suggested negative correlations between BMI and sexual functioning, however others did not. 5,[15][16][17] FSD attributed to obesity can be explained by the hormonal imbalance caused by insulin resistance, the atherosclerosis of the vasculature supplying the genitalia, in addition to the psychological incompetence caused by low self-esteem and lack of confidence due to imperfect body image.…”
Section: Discussionsupporting
confidence: 91%
“…Research examining the direct relationship between BMI and indicators of sexual health has yielded equivocal results to date. Specifically, three studies reported that sexual function and/or satisfaction both decrease as a function of increased BMI (Addis et al, 2006;Espositoetal.,2007;Milhausen,Buchholz,Opperman,&Benson,2015), whereas two found no significant correlation between the variables (Bajos, Wellings, Laborde, & Moreau, 2010;Weaver & Byers,2006).Giventheseinconsistentresults,furtherresearchseems necessary in order to disentangle the direct influence of actual body mass from women's experience of their bodies (i.e., positive and negative aspects of body image) on indicators of sexual health.…”
Section: Body Image and Sexual Healthmentioning
confidence: 99%